THE INVESTIGATION OF BEST PRACTICES ON SYMBOLIC MATHEMATICAL COMMUNICATION: A COMPARATIVE STUDY IN JAPAN, LAO PDR, AND THAILAND (Malaysian Journal of Learning and Instruction, 2024)
Purpose – This comparative study sought to identify best practices concerning symbolic mathematical communication between primary school teachers and students in Japanese, Laotian, and Thai classrooms.Method – The target groups were 18 teachers and 671 students in Grade 1 to Grade 6 mathematics classrooms in Japan, Lao PDR, and Thailand. A total of 18 classrooms were inspected, one from each grade; thus, the unit of analysis was a classroom. Research instruments included a video recorder, a camera, and field notes. The data was gathered by videotaping, photographing, and taking notes. A descriptive analytics method was used to examine the data, following Pirie's mathematical communication framework (Pirie, 1998).Findings – Based on cultural norms and educational approaches in each country, the country-specific practices of symbolic communication were found to differ significantly among the mathematics teachers from the three countries. Owing to the education system in Japan placing a strong emphasis on discipline and respect, their teachers were found to focus on students’ symbolic explanations, particularly allowing students to elaborate on the meaning of complex mathematical ideas and concepts using symbolic communication. Laotian teachers tended to explain the answers using symbolic mathematical communication. This is because the country-specific practices in the Laotian local context concerning mathematical concepts are contextualized to relate to students’ daily lives and experiences, making abstract symbols more meaningful. Finally, Thai teachers were found to focus on the students’ answers rather than the learning process or operations. This suggests that Thai teachers often focus on memorising and repeating of mathematical procedures and formulas.Significance – The study findings offer a substantial understanding of the role of culture in education by investigating symbolic communication in mathematics classrooms in Japan, Laos, and Thailand. This implies the potential to improve teaching practices,enhance student learning experiences, and promote cultural sensitivity and inclusion in educational settings.